Europeanization and bureaucratic autonomy in the new member states: a case study of the agricultural paying agency in Slovakia - Beblavy, Miroslav (2009)
The paper explores the impact of Europeanization on bureaucratic autonomy in the new EU member states using as a case study the Agricultural Paying Agency in Slovakia. the paper shows that Europeanization had limited sustained impact on the personal autonomy of senior officials; however, it requires and sustains the personal autonomy of an extensive cadre of mid-level and junior civil servants. At the same time, it necessitates and continues to sustain significant change in the way agricultural subsidies are distributed, with a high level of autonomy in implementation and a lower, but still significant, measure of autonomy in policy-making. These conclusions can also generally be supported by evidence from Lithhuania and Poland. In addition, the coercive elements of Europeanization interacted with the temporarily high bureaucratic autonomy in Slovakia to `open' non-coercive channels of Europeanization of agricultural subsidies and beyond. - Reproduced.
Keywords: European Union